2013
DOI: 10.4088/jcp.12m08099
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Methylphenidate for Apathy in Alzheimer’s Disease

Abstract: Objective In a recent crossover trial, methylphenidate treatment decreased apathy in Alzheimer's disease. We further assessed this finding in the Alzheimer's Disease Methylphenidate Trial (ADMET). Method Six-week, randomized, double-blind, placebo-controlled multicenter trial enrolling Alzheimer's disease participants (NINCDS-ADRDA criteria) with apathy assigned to methylphenidate 20 mg daily or placebo, conducted from June 2010 to December 2011. Primary outcomes were change in Apathy Evaluation Scale (AES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 28 publications
1
137
0
3
Order By: Relevance
“…This study supported the safety and efficacy of methylphenidate treatment for apathy in Alzheimer's disease. Two out of the 60 patients experienced serious adverse events consisting of delusions, agitation, anger, irritability, and insomnia [93].…”
Section: Methylphenidate Treatment In Depression and Dementiamentioning
confidence: 99%
“…This study supported the safety and efficacy of methylphenidate treatment for apathy in Alzheimer's disease. Two out of the 60 patients experienced serious adverse events consisting of delusions, agitation, anger, irritability, and insomnia [93].…”
Section: Methylphenidate Treatment In Depression and Dementiamentioning
confidence: 99%
“…Stimulants are another understudied area. Methylphenidate has also been used off-label for depression, and it may have benefits for apathy in AD in the absence of depressive features (Rosenberg et al 2013); however, stimulants have not been shown to improve cognition in randomized controlled trials of MCI or AD. Additional studies will need to examine whether methylphenidate may have positive effects for older depressed adults with comorbid cognitive impairment.…”
Section: Pharmacologic Approaches Antidepressantsmentioning
confidence: 99%
“…Notably, another study found that implementing a systematic approach to pain management in nursing homes led to significantly reduced agitation [84]. With respect to the treatment of apathy, two small studies suggest benefits from methylphenidate though accompanied by the expected adverse effects such as elevated blood pressure [85,86].…”
Section: Neuropsychiatric Symptoms Of Dementia (Neurocognitive Disordmentioning
confidence: 99%